Percutaneous transolecranon pinning and lateral pinning Vs lateral pinning in displaced supracondylar fractures of humerus in children: an observative study - Jindal, Ramesh Chand; Singh, Manjeet; Sandhu, H. S.; Bal, Gurwinder Singh; Ratna, Harish V. K.; Chawla, Jasneet S. (International Journal of Research in Medical Sciences, 2019)
Background: Supracondylar fracture (humerus) is type of extra-articular fracture occurring in the distal metaphyseal site of humerus. It is almost exclusively a fracture of the immature skeleton, seen in children and young teenagers. Fractures around the elbow are a great challenge to orthopaedic surgeons. Clinical diagnosis may be difficult due to noncooperative patient and massive swelling around the elbow. Displaced type of supracondylar fractures poses problem not only in reduction but also in maintenance of reduced fracture and rapid inclusion of nerves and vessels. Methods: The present study was conducted on 30 cases of displaced supracondylar fracture humerus in children, aged 2-14 years, who were treated by CRPP with either lateral entry of k-wires or a lateral wire and a vertical wire through olecranon (transolecranon). Results: Both the Groups achieved 90% satisfactory results, but 10% unsatisfactory results recorded in Group A only rather than in Group B. Conclusions: Although the transolecranon wire has the disadvantage of limiting the flexion and extension of the elbow, this does not influence the final-outcome much as the elbow is fixed in a POP splint for minimum 3 weeks-in all patients in both groups.